Renal Functional and Perioperative Outcomes of Off-Clamp vs. Clamped Robot-Assisted Partial Nephrectomy: Matched Cohort Study - Tanagho, Youssef S. (2012)
OBJECTIVE: To evaluate the potential benefit of performing off-clamp robot-assisted partial nephrectomy (RAPN) as it relates to renal functional outcomes, while assessing the safety profile of this unconventional surgical approach. METHODS: Twenty-nine patients who underwent off-clamp RAPN for suspected renal cell carcinoma at Washington University between 3/2008 and 9/2011 (group-1) were matched to 29 patients with identical nephrometry scores and comparable baseline renal function who underwent RAPN with hilar clamping during the same period (group-2). The matched cohorts' perioperative and renal functional outcomes were compared at a mean 9-month follow-up. RESULTS: Mean estimated blood loss was 146.4 cc in group-1, versus 103.9 cc in group-2 (p=0.039). Mean hilar clamp time was 0 minutes in group-1 and 14.7 minutes in group-2. No perioperative complications were encountered in group-1; one Clavien-2 complication (3.4%) occurred in group-2 (p=1.000). At 9-month follow-up, mean eGFR in group-1 was 79.9, versus 84.8 ml/min/1.73m(2) preoperatively (p=0.013); mean eGFR in group-2 was 74.1, versus 85.8 ml/min/1.73m(2) preoperatively (p<0.001). Hence, eGFR declined by a mean of 4.9 ml/min/1.73m(2) in group-1, versus 11.7 ml/min/1.73m(2) in group-2 (p=0.033). CONCLUSIONS: Off-clamp RAPN is associated with a favorable morbidity profile and relatively greater renal functional preservation compared to clamped RAPN. Nevertheless, the benefit is small in renal functional terms and may have very limited clinical relevance.